2015
DOI: 10.1007/s00244-015-0206-z
|View full text |Cite
|
Sign up to set email alerts
|

Dandelion (Taraxacum officinale) and Agrimony (Agrimonia eupatoria) as Indicators of Geogenic Contamination of Flysch Soils in Eastern Slovakia

Abstract: Contents of potentially toxic elements Fe, Mn, Cr, Ni, Co, V, Cu, and Mo were determined in common dandelion (Taraxacum officinale) and agrimony (Agrimonia eupatoria) to show their usefulness as bioindicators of geogenic soil pollution. Both plants were collected on geochemically anomalous soils developed on flysch sedimentary rocks (Paleogene) of Eastern Slovakia, which also are composed of weathered detritus of some ultramafic rocks. Generally, contents of the investigated association of potentially toxic el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
(36 reference statements)
3
12
0
Order By: Relevance
“…The statistically significant correlation between the concentration of the analysed metals in the soil and their content in leaves and roots of plants corroborates the literature data (Bini et al 2012; Collier et al 2010; Cook et al 1994; Čurlík et al 2016; Królak 2003) on the usefulness of species from the Taraxacum genus, including the Taraxacum section, in bioindication studies. It should also be noted that the studied species accumulated higher amounts of Zn, Mn and Fe in leaves compared to roots, while more Cu was accumulated in roots than in leaves.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The statistically significant correlation between the concentration of the analysed metals in the soil and their content in leaves and roots of plants corroborates the literature data (Bini et al 2012; Collier et al 2010; Cook et al 1994; Čurlík et al 2016; Królak 2003) on the usefulness of species from the Taraxacum genus, including the Taraxacum section, in bioindication studies. It should also be noted that the studied species accumulated higher amounts of Zn, Mn and Fe in leaves compared to roots, while more Cu was accumulated in roots than in leaves.…”
Section: Resultssupporting
confidence: 89%
“…Based on the ratio: the concentration of a metal in the root and the concentration of a metal in the soil, values of metal biological concentration factors (BCF) were calculated, while based on the ratio: the concentration of a metal in leaves and the concentration of a metal in the root, values of metal translocation factors (TF) were calculated (Čurlík et al 2016; Malik et al 2010). Canonical correspondence analysis (CCA) was performed to determine the effect of selected chemical indices on the cumulation and translocation factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is widely known that trace elements are not found in plant tissues with the same the proportion of their concentrations in soil [49]. The uptake of these elements by plants is selective: essential nutrients (like Zn, Cu, and Mn) are actively taken and show a more linear relation to soil concentration if compared to nonessential nutrient [47,50].…”
Section: Discussionmentioning
confidence: 99%
“…Low BAFs were also determined for Cr. Čurlík et al [47], who reported the low uptake of Co and Cr by T. officinale through both roots and shoots, as did Fröhlichová et al [24]. Low BAFs for As, Cr, and Zn, indicating the limited transport of these elements from soil contaminated by the multi-industry activities to root vegetables, were documented by Ahmed et al [48].…”
Section: Risk Element Accumulation and Mobility In Soilsmentioning
confidence: 85%